The prevalence of musculoskeletal pain and injuries in South African competitive Ballroom and Latin American dancers - Maddocks, Megan (My University, 2022)
OBJECTIVES: Lower limb injuries, specifically affecting the foot and ankle, are common in dance and relatively well documented in Ballet. There is very little research on Ballroom and Latin American dancing and the injuries sustained by those who participate in these styles of dance. This unique study provides insight into pain, injuries and problems faced by danced with a detailed focus on the foot and ankle. It also highlights habit regarding footwear practices and seeking medical attention when injured. METHODS: Musculoskeletal Pain Intensity and Interference Questionnaire for Musicians (MPIIQM) was modified to be specific to dancers and the survey was conducted with a sample of convenience from two major dance competitions in South Africa. Data was captured in Research Electronic Data Capture (RedCap) and analysed in Statistica. RESULTS: 12.7% response rate: 77% of dancers experienced pain at some point in their dance career, 69% in the last 12 months, 54% in the last month and 48% (n = 97) were in pain at the time of completing the survey at the competitions. 35% of pain (only) experienced in the foot and ankle (37% plantar aspect, 29% forefoot area). 26% of all pain, problems, and injuries were experience in the foot and ankle (28% plantar aspect, 22% hindfoot). Most dancers seek medical attention only sometimes, with a physiotherapy being the most common profession and over 30% of dancers never seek medical attention when injured. CONCLUSIONS: The first metatarsophalangeal joint area was an important anatomical structure that was affected by pain. There needs to be more research into the aetiology of Ballroom and Latin American dancing pain, problems, and injuries to guide improvements in training and technique to prevent them. The authors hopes that future research will include more detailed investigation into the foot and ankle as used here.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science Medicine in Sports and Exercise Science to the Faculty of Health Sciences, School of Therapeutic Sciences, University of Witwatersrand, Johannesburg, 2022